Human Resource Development as a Strategy to Face Environmental Change: A Thematic Interpretation Study of the Qur’an - Suhendar, Otong (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract This article aims to explain the strategy offered by the Qur’an in dealing with environmental change through the development of human resources. The method used in writing this article is the thematic method with a literature review, and it is qualitative. The results of the study show that the Qur’an provides solutions and guidance for humans in facing environmental changes, which, if applied in life, will enable them to adapt well. At least four approaches can be taken from the indications of the Qur’anic verses in this matter: strengthening spirituality, using reason and intellect to the fullest, enhancing environmental education, and developing skills. Keywords: Adaptation; Environmental Change; Human Resource Development.   Abstrak Artikel ini bertujuan untuk menguraikan tentang strategi yang ditawarkan Al-Qur’an dalam menghadapi perubahan lingkungan melalui pengembangan sumber daya yang dimiliki manusia. Adapun metode yang dipakai dalam penulisan artikel ini adalah metode tematik dengan kajian pustaka serta bersifat kualitatif. Hasil kajian menunjukkan bahwa Al-Qur’an memberi solusi dan petunjuk bagi manusia dalam menghadapi perubahan lingkungan, yang jika diaplikasikan dalam kehidupan akan mampu beradaptasi dengan baik. Setidaknya ada empat tawaran yang dapat diambil dari isyarat ayat-ayat Al-Qur’an dalam hal ini, yaitu penguatan spiritualitas, penggunaan akal dan nalar secara maksimal, penguatan edukasi lingkungan dan pengembangan keterampilan. Kata Kunci: Adaptasi; Pengembangan SDM; Perubahan Lingkungan.